Cefazolin and moxalactam pharmacokinetics after simultaneous intravenous infusion. - Polk, R E (1981)
A high-performance liquid chromatographic method for the measurement of moxalactam concentrations in serum was modified to permit the simultaneous measurement of both moxalactam and cefazolin. We then studied whether the simultaneous administration of both moxalactam and cefazolin to normal subjects would produce profiles of serum concentration versus time which were the same as those obtained after the administration of each drug individually. Six healthy adults received a 30-min infusion of cefazolin (10 mg/kg), followed in 2 days by the same dose of moxalactam. After 2 days, both antibiotics were administered together. A two-compartment model was found to adequately characterize the data, and the serum concentration curve for each drug when given alone was statistically identical to that obtained after simultaneous administration. Cefazolin was found to produce a significantly greater peak serum concentration (105 +/- 14 versus 81 +/- 21 microgram/ml) and a significantly greater area under the curve (218 +/- 42 versus 157 +/- 19 . microgram h/ml). The terminal half-life of moxalactam was not significantly longer than for cefazolin (2.2 +/- 0.6 versus 2.0 +/- 0.6 h, respectively). The method of simultaneous administration may have distinct advantages over conventional methods for studies of comparative tissue penetration.